Real retouching : a professional step-by-step guide - Beene, Carrie (Burlington, MA : Focal Press, 2011)
From the perfect glossy pages of a magazine to the larger-than-life images floating on a billboard in the sky, image retouching has become a key component of today's digital photography world. So popular, in fact, that the sheer act of retouching has become its own verb as we often ask ourselves, "I wonder if this image was Photoshopped?" Sometimes controversial but widely accepted, and even expected, excellent retouching skills are crucial to finding success in the field of digital imaging. As you work through the clear step-by-step instructions in the book using the images provided on the bonus CD, you'll learn how to do real retouching jobs from start to finish, including each and every technical step along the way.
Includes index and 1 CD
MA
Keywords: Photography -- Retouching